2022
DOI: 10.3390/en15031155
|View full text |Cite
|
Sign up to set email alerts
|

The Fire Resistance and Heat Conductivity of Natural Construction Material Based on Straw and Numerical Simulation of Building Energy Demand

Abstract: The motivation for research to help address climate change is a continuous process of searching for eco-friendly materials in the building industry, which will allow minimizing the negative impact of this sector on the environment. The main objective of the paper is to assess the properties of a natural resource such as straw as an eco-friendly material in various variants for use in low-energy demand construction. The research results will fill the knowledge gap in the field of numerical analyses of the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, other authors report a variability of the thermal conductivity of materials; for example, humidity is an essential factor, and its increase is directly proportional to the thermal conductivity. Yapin Zhou et al, reported results between 0.03-0.1 (W/mK), while other authors have reported results for lignocellulosic materials of 0.033 and 0.065 and 0.07 and 0.08 (W/mK) at different densities, achieving in some cases values over 400 (kg/m 3 ) [1,16,20,21,26,57]. It is important to note that the research mentioned above generates materials in a rigid or panel format, unlike the proposal, which uses a much less commonly used method: the blowing method.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, other authors report a variability of the thermal conductivity of materials; for example, humidity is an essential factor, and its increase is directly proportional to the thermal conductivity. Yapin Zhou et al, reported results between 0.03-0.1 (W/mK), while other authors have reported results for lignocellulosic materials of 0.033 and 0.065 and 0.07 and 0.08 (W/mK) at different densities, achieving in some cases values over 400 (kg/m 3 ) [1,16,20,21,26,57]. It is important to note that the research mentioned above generates materials in a rigid or panel format, unlike the proposal, which uses a much less commonly used method: the blowing method.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it is observed that the thermal conductivity of the mixture increases as the density increases, similar to other lignocellulosic fiber materials but different to other conventional materials that decrease their thermal conductivity as they have a higher density. Figure 8 shows the results of the measurement at different density levels, wh can be observed that the mixture has a thermal conductivity lower than 0.041 (W which demonstrates its potential as a thermal insulating material, since this value is parable with conventional insulating materials in the current market [1,11,16,20,26] thermore, it is observed that the thermal conductivity of the mixture increases as the sity increases, similar to other lignocellulosic fiber materials but different to other con tional materials that decrease their thermal conductivity as they have a higher dens According to these results, and considering that cellulose is usually blown into tical elements at densities between 50-90 (kg/m 3 ) [48], it was decided to restrict the de variable between 60-90 (kg/m 3 ) and to work with mechanically processed wheat stra the second stage of tests, thus obtaining the thermal conductivities shown in Figure According to these results, and considering that cellulose is usually blown into vertical elements at densities between 50-90 (kg/m 3 ) [48], it was decided to restrict the density variable between 60-90 (kg/m 3 ) and to work with mechanically processed wheat straw for the second stage of tests, thus obtaining the thermal conductivities shown in Figure 9.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 3 more Smart Citations